PENGEMBANGAN ALAT PERMAINAN EDUKATIF PEROSOTAN ARITMATIKA (PETIK) UNTUK MENINGKATKAN KEMAMPUAN BERHITUNG ANAK USIA 5-6 TAHUN - Siti Nurhatijah; Hariyanto Hariyanto; Tri Wahyu Martiningsih (Atthufulah : Jurnal Pendidikan Anak Usia Dini, 2022)
This study aims to develop products in the form of appropriate and effective learning media used for learning to count, especially basic addition and subtraction for children aged 5-6 tahun years. The method used in this research is R&D (research and development), namely product development in the form of an arithmetic slide educational game tool (PETIK) and data collection techniques used are observation, interviews, documentation and validation questionnaires form material experts, media and learning experts. The data analisys technique used in this study used descriptive analisys of percentages. The results of this study indicate that the arithmetic slide educational game tool (PETIK) has met the criteria for being very feasible and effective in being used in learning activities to improve the numeracy skills of children aged 5-6 years.